A systematic review and meta-analysis of phase III randomized controlled trials to assess the risk of pneumonia, URTIs, and VTE in multiple myeloma patients treated with isatuximab - Daniel Thomas Jones; Hazem Aboaid; Ramaditya Srinivasmurthy; Kevin Nguyen; Rishi Kumar Nanda; Jason Ta; Benjamin Tzer-Ming Chuang; Yin Mon Myat; Aishwarya Hanspal; Kyaw Zin Thein; Thura Win Htut (Exploration of Targeted Anti-tumor Therapy)
Background: Multiple myeloma (MM) is a hematologic malignancy characterized by the clonal proliferation of malignant plasma cells in the bone marrow, constituting approximately 13% of all hematologic malignancies. Isatuximab is a monoclonal antibody targeting the CD38 protein on myeloma cells, causing cell death through various immune-mediated mechanisms. Clinical trials have shown that adding isatuximab to standard regimens for MM significantly enhances efficacy but introduces some notable toxicities. The purpose of this study is to determine the risk of pneumonia, upper respiratory tract infections (URTIs), and venous thromboembolism (VTE) in patients with MM treated with isatuximab. Methods: We conducted a comprehensive literature search using Medline, Embase, and Cochrane databases from inception through July 22nd, 2024. Phase III randomized controlled trials (RCTs) utilizing isatuximab in newly diagnosed MM (NDMM) and relapsed and refractory MM (RRMM) reporting pneumonia, URTIs, and VTE as adverse events were included. Mantel-Haenszel (MH) method was used to calculate the estimated pooled risk ratio (RR) with 95% confidence interval (CI). Heterogeneity was assessed with Cochran’s Q-statistic. Random effects model was applied. Results: A total of 1,044 patients from three phase III RCTs (ICARIA-MM, IKEMA, IMROZ) were included for pneumonia and URTI analysis, while 1,403 patients from three trials (IKEMA, IMROZ, GMMG-HD7) were included for VTE evaluation. The incidence of any-grade pneumonia was higher in the isatuximab group (30.1% vs. 23.2%; RR, 1.31; 95% CI 1.06–1.61; P = 0.01), as was high-grade pneumonia (20.8% vs. 15.3%; RR, 1.38; 95% CI 1.06–1.81; P = 0.02). No statistically significant differences were observed between the isatuximab and control groups for any-grade URTIs, high-grade URTIs, or VTE. Discussion: This meta-analysis highlights a significant increase in the incidence of pneumonia with the addition of isatuximab to standard myeloma regimens, underscoring the need for routine antibiotic prophylaxis, thromboprophylaxis, vigilant monitoring and early intervention to mitigate these risks.